THE INFLUENCE OF THE STEAM APPROACH ON THE PjBL MODEL ON STUDENTS' COLLOID LEARNING OUTCOMES - Sugiarti, Sugiarti; Sulastri, Taty; Fatimah, Syarifah (UNESA Journal of Chemical Education, 2024)
Chemistry learning at SMA Negeri 7 Takalar is still dominated by teacher-centered learning. Students still have difficulty understanding chemistry lessons such as colloids, the material of which is conceptual in nature and requires contextual application of concepts. Therefore, it is very important to carry out learning that involves students actively applying colloid theory and concepts through the STEAM approach in the Project Based Learning learning model. This research is quasi-experimental research that aims to determine the colloid learning outcomes of students after learning with the STEAM approach in the PjBL Model for Class XI MIPA SMA Negeri 7 Takalar. Posttest only control group design research design. The population is all class XI students consisting of three classes. The results of inferential statistical tests show that student learning outcomes using the t-test at a value of α = 0.05 obtained a value of tcount > ttable (2.83 > 1.99) and the research samples for Class XI MIPA 2 and Class XI MIPA 3 as experimental and control groups were randomly selected. The results of the descriptive analysis show that the completeness of learning outcomes for the experimental class is 72.73% higher than the control class, 48.48%. This means that H0 is rejected and H1 is accepted, thus it can be concluded that the STEAM approach in the Project Based Learning Model has a significant influence on the colloid learning outcomes of class XI MIPA students at SMA Negeri 7 Takalar.